Challenges of Islamic Insurance - Abidi, Ilyes; Nsaibi, Mariem; Regaieg, Boutheina (International Journal of Economics and Financial Issues, 2020)
The aim of this paper is to study the stability of insurance companies. The majority of works on this topic has focused on the determinants of financial stability. Therefore, they interested in the Z-score, focused on the ROA, as well as the panel method. Unlike previous work, we have formed a score made up of indicators of efficiency, effectiveness, profitability, solvency, productivity, investment and risk, as well as macroeconomic indicators. Our sample consists of 30 insurance companies, 15 of which are shariaa compatible. The choice of these companies is justified by their contribution to the total assets of the both types of finance. This selection method allowed us to have a global idea on the effectiveness, efficiency, risk and stability of the two insurance sectors. The analysis of the stability scores, determined using the scoring and logit transformation method, revealed that Islamic insurance companies are more stable than conventional insurance companies. From a risk perspective, Islamic insurance companies are less risky than conventional insurance companies. They lose, on average, 1.598% of their assets against 3.704% for conventional insurance companies. This observation related to three types of risk, namely; liquidity risk, market risk and credit risk. Furthermore, this empirical investigation revealed that takaful companies are not immune to the toxic funds of the crisis. Likewise, we note that Islamic insurance companies are sensitive to political shocks such as that of the Arab revolutions that took place in 2011. Keywords: Effectiveness, Efficiency, Stability, Islamic Insurance and Conventional Insurance JEL Classifications: C62, G01, G22 DOI: https://doi.org/10.32479/ijefi.9860